Crystal structures and in vitro biological effects of two protocatechuic acid complexes. (12th October 2016) - Wei, Jinrui; Nong, Wenqian; He, Chunping; Zhou, Yong; Lu, Dongwei; Lin, Cuiwu
ABSTRACT: Piperazine (PRZ ) and ligustrazine (TMP ) were respectively in combination with protocatechuic acid (PA ) to form complexesI andII . The structures of complexesI andII were confirmed by 1 H NMR, 13 C NMR, and single crystal X-ray diffraction. The effects ofPA and its complexes on chondrocytes growth were measured using the MTT assay. Furthermore, the anticoagulant activities ofPA and two complexes were evaluated by four coagulation assays (PT, APTT, TT, and FIB). This study indicates that concurrently usingPA andTMP may have novel therapeutic uses in age-​related disorders such as osteoarthritis and cardiovascular disease.